Response surface methodology for optimization of production of lovastatin by solid state fermentation - Pansuriya,Ruchir C. (2010)
Lovastatin, an inhibitor of HMG-CoA reductase, was produced by solid state fermentation (SSF) using a strain of Aspergillus terreus UV 1718. Different solid substrates and various combinations thereof were evaluated for lovastatin production. Wheat bran supported the maximum production (1458 ± 46 µg g-1 DFM) of lovastatin. Response surface methodology (RSM) was applied to optimize the medium constituents. A 2(4) full-factorial central composite design (CCD) was chosen to explain the combined effects of the four medium constituents, viz. moisture content, particle size of the substrate, di-potassium hydrogen phosphate and trace ion solution concentration. Maximum lovastatin production of 2969 µg g-1 DFM was predicted by the quadratic model which was verified experimentally to be 3004 ± 25 µg g-1 DFM. Further RSM optimized medium supplemented with mycological, peptone supported highest yield of 3723.4±49 µg g-1 DFM. Yield of lovastatin increased 2.6 fold as with compared to un-optimized media.